DISCOURSE OF GENDER INEQUALITY AND DISCRIMINATORY “KELUARGA BERENCANA” PROGRAM IMPLEMENTATION AGAINST WOMEN (STUDY OF CRITICAL DISCOURSE ANALYSIS IN THE CONVERSATION INDONESIA) (International Conference on Social and Islamic Studies, 2022)
The Family Planning (KB) Program is a national-scale government program that was initiated in the 1970s. The aim is to reduce the birth rate and control population growth in Indonesia. The National Population and Family Planning Agency (BKKBN) reported that the national KB program services in the past year had exceeded 120 percent – ​​or exceeded the target. However, without realizing it, the practice of family planning programs turns out to be gender biased and discriminatory against women. The participation rate of women in the use of contraception is 96.7%, while the participation rate of men is only 3.3%. This study aims to explore the discourse on the implementation of KB programs that are gender unequal and discriminatory against women in an article in The Conversation Indonesia. This research method uses the Critical Discourse Analysis framework of the Teun Van Dijk model at the level of text, social cognition, and social context. This study also uses a qualitative approach. This study describes the analysis of the dimensions of the text, which consists of macro structure (thematic), superstructure (thematic), and micro structure (semantic, syntactic, stylistic, and rhetorical), analysis of social cognition, and analysis of social context in an article written by Robiatul Adawiyah in the media of The Conversation Indonesia with the title “Are We Aware That the Implementation of KB is Gender Lame and Discriminatory against Women?”. The results of this study indicate that the article on the discourse on the implementation of the family planning program which is gender unequal and discriminatory against women fulfills the three elements emphasized in Van Dijk's critical discourse analysis. Socially cognitively, the author of the article also fulfills Van Dijk's Social Cognition Analysis Model/Scheme which consists of Person Schemas, Self Schemas, Role Schemas, and Event Schemas.